If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28x + -7 = 49 Reorder the terms: -7 + 28x = 49 Solving -7 + 28x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 28x = 49 + 7 Combine like terms: -7 + 7 = 0 0 + 28x = 49 + 7 28x = 49 + 7 Combine like terms: 49 + 7 = 56 28x = 56 Divide each side by '28'. x = 2 Simplifying x = 2
| 12x^2-176x+480=0 | | 1=1/3a-5 | | 4=2.6x | | 3(17)-(9n)=24 | | 2ln(x-2)-ln(x^2-4)+ln(3)=0 | | -2(y-3)+y=12 | | 5f+2=-4+2f-8 | | 2.75+.003+.158=2.938 | | 9m-2m=77 | | 4g+g=12 | | 3a-2a=12 | | 4xz=2104 | | 700/15 | | 3x+x=1 | | 1/cotu | | 5f+2=-42f-8 | | 2sectheta-2/1-costheta=2sectheta | | n+72=180 | | 6a+9=8 | | 55b^2-155b-30= | | 50/y=y/2 | | Mx=8 | | -31-3p=7+4(8+8p) | | 22+t=72 | | c+(-8+6c)=0 | | 16(4y-5)=8(7y+5) | | 5x-7/3=xx | | 5x-7u/2=2u-; | | -2(x-3)(x+3)-18=0 | | 3(5w-2)-4(3w-5)=w | | 28-x+30-x+3x+x=40 | | -7+6.5(1+2.5s)=-16.5 |